2023
DOI: 10.7759/cureus.36816
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lactate-Albumin Ratio: Soothsayer for Outcome in Sepsis

Abstract: Aim: The aim of this study is to assess the efficacy of the serum lactate/albumin (L/A) ratio as a prognostic marker of sepsis syndrome.Materials and methods: This study was conducted in the Internal Medicine Department at Acharya Vinoba Bhave Rural Hospital with a sample size of 160 cases of sepsis. The serum L/A ratio was calculated on admission and correlated with deaths and morbidity. Statistical analysis was significant if the P-value was less than 0.05.Results: The mean age of patients was 52.83 ± 16.80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Although Li et al incorporated additional variables, notably interleukin-6, and achieved a slightly higher AUC, our study offered a focused analysis solely on early serum markers, asserting the paramount importance of L/A in predicting 28-day sepsis outcomes. Similarly, Kabra et al [ 19 ] reported high specificity and sensitivity for L/A, which is consistent with our findings. However, our study provides a comprehensive evaluation, leveraging a larger sample size and a broader time frame, ensuring more robust and generalizable conclusions regarding the predictive capacity of the L/A ratio in sepsis prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Although Li et al incorporated additional variables, notably interleukin-6, and achieved a slightly higher AUC, our study offered a focused analysis solely on early serum markers, asserting the paramount importance of L/A in predicting 28-day sepsis outcomes. Similarly, Kabra et al [ 19 ] reported high specificity and sensitivity for L/A, which is consistent with our findings. However, our study provides a comprehensive evaluation, leveraging a larger sample size and a broader time frame, ensuring more robust and generalizable conclusions regarding the predictive capacity of the L/A ratio in sepsis prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, a model incorporating more variables may offer improved predictive capability compared to a single lactate variable. Recently, a study suggested that compared to lactate and albumin alone, the predictor value of the lactate and albumin ratio was outstanding in predicting death and hospital stay (discharge) among sepsis participants, with a sensitivity of 100% and a specificity of 88% [147]. As most of the included studies are observational, they cannot infer causation.…”
Section: Discussionmentioning
confidence: 99%